Tradition et identité alimentaire : discours médiatiques sur La Binerie Mont-Royal - Gwenaëlle Reyt (Communiquer)
Open since 1938, La Binerie Mont-Royal is a tiny restaurant in Le Plateau Mont-Royal in Montréal. This ordinary and unpretentious establishment became famous in the 1980s with the novel and the movie Le Matou. Since then, the restaurant is a tourist destination that offers the experience of another time and authentic Quebecois food. This article proposes to analyze media discourses to explore the construction of the image of La Binerie as an attractive space of traditional and food identity. The emergence of this identity cannot, however, be understood without placing it in a general context of a quest for national identity, the repositioning of Quebec gastronomy and the rebirth of a popular district.